STUDI KOMPARASI DESAIN USER INTERFACE PLATFORM STREAMING PADA SMARTPHONE (STUDI KASUS: iQIYI DAN WeTV) - Widyastuti, Dyah Isna; Hasyim, Noor; Yogananti, Auria Farantika (Universitas Mercu Buana, 2023)
The presence of streaming applications is one of the positive impacts of the progress of the internet which is increasingly developing in a modern direction. This can be seen from the ease with which users can access the application via smartphone without being limited by distance and time. The first thing the user sees is the application's user interface (UI), which is the interface between the user and the application system. This research aims to compare the UI designs of the iQIYI and WeTV applications on smartphones to measure and see to what extent the application user interface (UI) can be used well. The user interface in the application will be analyzed formally and then use the theory of the Golden Rules of User Interface Design by Theo Mandel, namely placing the user in control, making it easier for the user to remember, and consistency of the interface. This research uses descriptive qualitative methods supported by observation and literature study. The results produced in the research are evaluation results which can be used as consideration in improving the application, both in terms of UI design and application performance.